Land values as the social construction of scarcity. - Davy, Benjamin (TU Wien, 2016)
Land values reflect the social construction of scarcity. The polyrational theory of property and land values (B. Davy 2012 and 2014) helps planners and other policymakers understand how different perceptions of land values influence scarcity judgments. The notion of exchange value explains scarcity in terms of demand exceeding the supply of land in desirable locations. The notion of use value explains scarcity with respect to the range of individual and social utility (J. Bentham) or capabilities (A. Sen, M. Nussbaum) rendered by land available for desirable uses. The notion of territorial value explains scarcity as a function of spatial power gained through territorial sovereignty or land use rights. The notion of existence value explains scarcity with a view to the ecological functions of land (A. Leopold). The four social constructions of scarcity sometimes overlap: Superb environmental quality may result in higher prices of building land which is not exposed to fumes or noise, but located near a pristine forest or an attractive lake. The four social constructions of scarcity, however, are fundamentally different from each other. A scarcity of spatial commons such as public streets or public parks cannot be expressed in exchange values of streets and parks (but rather in the dissatisfaction of users). Accordingly, planners cannot manage scarcity easily, and certainly not through a simple trade-off between different types of land values. Polyrational scarcity management requires that planners be critically aware of plural land values and a mounting pressure to choose judiciously from their tool-box of available instruments.
Keywords: Raumplanung; Raumtheorie; Bodenwert; Nutzwert; Planungstheorie; Knappheit; Wertbemessung; Eigentumswert